Job Creation and Labor Reform in Latin America - Kaplan, David S. (2012)
This paper studies the effects of labor-regulation reform using data for 10,396 firms from 14 Latin American countries. Firms are asked both how many permanent workers they would have hired and how many they would have terminated if labor regulations were made more flexible. I find that making labor regulations more flexible would lead to an average net increase of 2.08 percent in total employment. Firms with fewer than 20 employees would benefit the most, with average gains in net employment of 4.27 percent. Countries with more regulated labor markets would experience larger gains in total employment. These larger gains in total employment, however, would be achieved through higher rates of hiring and higher rates of termination. These results may explain why there is substantial opposition to labor reforms despite the predicted gains in efficiency and total employment.